The Governments' Role in Preserving National Identity on Globalization - Yarmuhammat Xudayberganovich, Madaliev; Ahmadov , Agil; Karomi, Karomi (Journal of Sustainable Development and Regulatory Issues (JSDERI), 2025)
This study explores how governments play a pivotal role in safeguarding national identity amid the transformative forces of globalization, offering comparative insights from Asian and European nations. As globalization accelerates the flow of information, culture, and economy across borders, it challenges states to maintain and protect their national identity. In response, this research analyzes how governments in both regions design and implement policies to confront these challenges. Using a qualitative design with a comparative approach, the study examines academic literature, policy documents, and selected case studies. The findings fall into three key sections. First, cultural policy reveals that Asian governments preserve tradition through education and cultural festivals, while their European counterparts prioritize legal protections for cultural heritage. Second, political strategies show that Asian nations implement centralized, state-driven measures, whereas European countries pursue multilateral consensus. Third, the analysis of media and technology highlights a striking contrast: Asian governments actively regulate local media to shape cultural narratives, while European governments protect freedom of expression within democratic frameworks. The study concludes that, although their methods differ, both regions empower governments as central actors in preserving national identity. These findings underscore the importance of balanced policies that promote global integration without compromising cultural identity.